c-Src phosphorylation and activation of hexokinase promotes tumorigenesis and metastasis - Jia Zhang; Suili Wang; Bin Jiang; Lihong Huang; Zhiliang Ji; Xiaotong Li; Huamin Zhou; Aidong Han; Ai Chen; Yanan Wu; Huanhuan Ma; Wentao Zhao; et al. (Nature Communications, 2017)
The protein tyrosine kinase c-Src is a renowned proto-oncogene with pleiotropic effects. Here, the authors show that c-Src induces the metabolic reprogramming of cancer cells by phosphorylating hexokinases HK1 and HK2, which in turns lead to increased HK catalytic activity and consequent enhancement of glycolysis.